NAVIGATING THE MERDEKA CURRICULUM: ENGLISH TRANSFORMATIONAL TEACHERS' CHALLENGES WITH PROJECT-BASED LEARNING - Nurohmah, Karina; Nurjamin, Lucky Rahayu; Hamzah, Amir (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
Implementing project-based learning in the classroom remains a significant challenge for educators. In response, numerous studies have been conducted on the challenges of implementing this method. This study focuses on English transformational teachers' challenges in implementing project-based learning within the Merdeka Curriculum. This study aims to identify the challenges English transformational teachers face in implementing project-based learning at the middle and upper education levels in Garut, West Java, Indonesia. A descriptive qualitative approach with a case study design was used in this research. Data collection was conducted through interviews. The data were analysed using Marx et al.'s theory and the Miles formula, which included data reduction, data display, and conclusion drawing/verification. The results showed that of the six challenges proposed by Marx et al., three significant challenges faced by English transformational teachers in implementing project-based learning were time management, controlling and supporting student learning, and school facilitation. Despite being English transformational teachers, the findings indicate that integrating project-based learning into the Merdeka Curriculum remains challenging.